2018
DOI: 10.17998/jlc.18.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemolipiodolization for Hepatocellular Carcinoma with Central Bile Duct Invasion Causing Conjugated Hyperbilirubinemia: Safety and Prognostic Factors for Survival

Abstract: Background/Aims: The treatments and outcomes of hepatocellular carcinoma (HCC) with bile duct invasion are not well known. We aimed to confirm the safety of transarterial chemolipiodolization (TACL) and identify prognostic factors for patients with bile duct invasion treated with TACL.Methods: Fifty patients with central bile duct invasion treated with TACL between 2005 and 2017 were enrolled. Patients were divided into three groups: hyperbilirubinemia (total bilirubin ≥2.5 mg/dL) with pre-TACL biliary drainag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Aside from survival results, tumor response rate and local recurrence rate also achieved desirable goals in this study. Upon first post-treatment imaging evaluation, historical data of TACE provided only 2–4%, 21–38%, and 24–37% in CR, PR, and progressive disease (PD) rates separately [ 3 , 28 , 29 , 35 ]. The current study showed that the first post-treatment imaging evaluation’s CR, PR, and SD rates were 20%, 65%, and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from survival results, tumor response rate and local recurrence rate also achieved desirable goals in this study. Upon first post-treatment imaging evaluation, historical data of TACE provided only 2–4%, 21–38%, and 24–37% in CR, PR, and progressive disease (PD) rates separately [ 3 , 28 , 29 , 35 ]. The current study showed that the first post-treatment imaging evaluation’s CR, PR, and SD rates were 20%, 65%, and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%